OP0080 Impact of Persistent Minimal Disease Activity on Long-Term Outcomes in Psoriatic Arthritis: Results from 5 Years of the Long Term Extension of A Randomized, Placebo-Controlled, Study. (10th June 2014) - Kavanaugh, A.; McInnes, I.; Mease, P.; Krueger, G.; Gladman, D.; Xu, S.; Tang, L.; Van Beneden, K.
Abstract : Background: Although criteria for Minimal Disease Activity (MDA) in psoriatic arthritis (PsA) have been developed and validated, a paucity of data concerning the impact of reaching MDA on long-term outcomes remains. Objectives: We assessed this concept using 5 yr long term extension (LTE) data from the GO-REVEAL study of PsA pts treated with golimumab (GLM). Methods: Data were obtained from the open label LTE of GO-REVEAL, a double-blind, PBO controlled Ph3 study comparing the efficacy and safety of GLM 50 mg and 100mg q4wks to PBO in pts with active PsA (≥3 swollen, ≥3 tender joints, and psoriasis). Pts with <10% improvement in both tender and swollen joints could enter early escape at wk16; all pts received GLM from wk24 forward. Last GLM injection was at wk252. MDA was defined as the presence of ≥5 of the following: ≤1/66 swollen joints; ≤1/68 tender joints; PASI score ≤1; pt pain VAS ≤15 (0-100); pt global assessment of disease activity VAS ≤20 (0-100); HAQ-DI ≤0.5; ≤1 tender enthesis point. 1 These criteria were assessed at wks 14, 24, 52, 104, 148, 196, and 256. Pts were selected who never achieved MDA and who achieved persistent MDA (defined as MDA for at least 3 consecutive time points) through Wk 256. Comparisons between patients who achieved/did not achieve MDA and the relationship between HAQ-DI or radiographic progression measured using vdHS scores were performed. These analyses utilized observed data from randomized pts. Statistical tests used ANOVA with Van der Waerden normal score and chi-squared test. Results: At the end of the PBO-controlled period until wk24, MDA was achieved in 7.7% and 28.1% of pts in the PBO and GLM groups, respectively. Through wk256, MDA was achieved in 44.2%>51.7% of pts (Table 1 ). Irrespective of treatment randomization, a better clinical meaningful HAQ improvement and less radiographic progression were observed in pts who achieved persistent MDA compared to pts who never achieved MDA (Table 2 ). While stratifying for treatment, pts achieving persistent MDA, who crossed-over from PBO to GLM, experienced similar HAQ improvement and radiographic outcomes compared to pts randomized to the GLM groups (Table 2 ), suggesting that delayed initiation with GLM did not result in a worsening of physical function or radiographic progression. In contrast, for pts not achieving MDA, delayed start with GLM resulted in numerically less radiographic benefit Conclusions: The data of the current analysis show that MDA occurred in approximately 50% of pts receiving effective treatment through 5 years. Aiming for MDA may serve as an argument for a treat-to-target strategy since persistent MDA can improve long-term functional and radiographic outcomes in pts with active PsA. References: Coates LC et al.Arthritis Car Res 2010;62:965-9. Disclosure of Interest: A. Kavanaugh Grant/research support: Abbott, Amgen, Janssen, and UCB, I. McInnes Grant/research support: Abbott, BMS, Janssen, Pfizer, Roche, Merck/Schering-Plough, and UCB., P. Mease: None declared, G. Krueger Consultant for: AbbVie, Amgen, Janssen, L'Oreal, Novartis, Pfizer, Vascular Biologics Limited., Speakers bureau: AbbVie, Amgen, Janssen, L'Oreal, Novartis, Pfizer, Vascular Biologics Limited, D. Gladman Grant/research support: AbbVie, Amgen, Celgene, Janssen, Lily, Novartis, Pfizer, and UCB, Consultant for: bbVie, Amgen, Celgene, Janssen, Lily, Novartis, Pfizer, and UCB, S. Xu Employee of: Janssen Research & Development, LLC, L. Tang Employee of: Janssen Research & Development, LLC., K. Van Beneden Employee of: Janssen Biologics BV DOI: 10.1136/annrheumdis-2014-eular.2254